A History of Board Certification in Pediatric Pathology on Its 30th Anniversary. (January 2021) - Goldstein, Jeffrey D.; Parham, David M.
In 1983 under the leadership of Dr. Daria Haust, the Pediatric Pathology Club (PPC; forerunner of the Society for Pediatric Pathology [SPP]), promulgated bylaws that included recognition of the special expertise required in pediatric pathology. This standard followed formal discussion that began as early as 1970, suggesting that special certification should be pursued, and the idea was vetted by the PPC in 1980 following a special report by Dr. Benjamin Landing and a letter to PPC members. Under the leadership of Dr. William Donnelly in 1984, a relationship between the SPP and the American Board of Pathology (ABPath) began in order to receive recognition of pediatric pathology as a special discipline. As a result, a test committee chaired by Dr. Jerald Schenken began preparing question categories and examples for ABPath examination. These efforts culminated in the first pediatric pathology subspecialty examination, held in Atlanta, Georgia on November 20, 1990. With this article we wish to detail the history of ABPath pediatric pathology board certification from its beginnings to the current time.